Aminolevulinic Acid Dehydratase Allelic Frequency and Lead Toxicity in Children Under-Five in a Former Used Lead-Acid Battery Area - Irawati, Yana; Kusnoputranto, Haryoto; Achmadi, Umar Fahmi; Safrudin, Ahmad; Sitorus, Alfred; Risandi, Rifqi; Wangsamuda, Suradi; Permana, Dendi Hadi; Syahrani, Lepa; Dewayanti, Farahana Kresno; Asih, Puji B S; Syafruddin, Din (UI Scholars Hub, 2022)
Polymorphisms in the Aminolevulinic Acid Dehydratase (ALAD) gene responsible for the ALAD1 and ALAD2 alleles have been implicated in susceptibility to lead toxicity. This study aimed to determine the allelic frequency of ALAD2 among children living in Bogor District, Indonesia, and its association with blood lead levels (BLLs) and lead toxicity. A cross-sectional study involving 128 children was conducted during September-October 2019 in the former ULAB area in Cinangka Village. The ALAD polymorphism, BLLs, and hematological parameters were evaluated. Blood samples were taken for dried blood spotting on filter paper, blood film, and BLL measurement. The PCR amplification and sequencing of the genomic DNA revealed the presence of two forms of the ALAD2 allele: 177C and 177T with a frequency of 0.05. Analysis of the correlation between the ALAD2 allele, BLLs, and basophilic stippling revealed that ALAD2 carriers had a five times higher risk of high BLLs, (OR = 5.359, p-value = 0.155) and had a slightly higher risk of exhibiting basophilic stippling (OR = 1.09, p-value = 1.000). Although not statistically significant, these findings suggested that the ALAD genotype may modify BLLs and lead to toxicity. The ALAD2 allele(177T) is firstly reported in any population in the world.